Sulla (Hedysarum coronarium L.) Response to Drought Stress during Early Vegetative Stage - Roberta Rossi; Mariana Amato; Salvatore Claps (Plants, 2023)
Sulla (Hedysarum coronarium L.) is a Mediterranean biannual anthelmintic forage. Due to its high productivity, nutraceutical value, and suitability for harsh environments, interest in this crop is growing. Under the current scenario of climate change and water scarcity, it is important to evaluate crop drought tolerance, especially for newly bred materials. Drought stress and well-watered conditions (50 vs. 80% of the field capacity) were applied in a pot experiment to compare responses of the widespread commercial variety Bellante with those of a recently released variety named ‘Centauro’, currently registered in the Italian national register of plant varieties but not yet available on the market. Compared to the well-watered treatment, drought-stressed plants showed lower values of fresh biomass (−69%), number of leaves (−68%), and root length (−49%). The Centauro cv. showed a different architecture to Bellante with more shoots (+43% P < 0.05) and a trend for more leaves (+25% P = 0.08). These traits are possibly related to its superior palatability. Centauro also developed a higher root length (+70%, P < 0.05) across irrigation levels. Drought stress affected condensed tannin (CT) content. A significant genotype × environment interaction was found with Centauro displaying more (+50%) and less (−35%) CT than Bellante under drought stress and well-watered conditions, respectively. The higher constitutive root length density of Centauro may be exploited in breeding programs aimed at improving the root sink, given the role of this trait in resource acquisition capacity and root-derived ecosystem services.